Investigating emission characteristics and combustion performance of a CRDI engine utilizing novel biodiesel derived from waste cooking oil and pentanol blends - M. Selvam; N. Pragadish; K. A. Harish; R. Ganapathy Srinivasan; Yuvarajan Devarajan; Nandagopal Kaliappan (Scientific Reports)
Abstract This study investigates an innovative approach by utilizing biodiesel derived from Waste Cooking Oil (WCO) to evaluate its impact on engine performance, combustion dynamics, and emissions characteristics. It examines the effects of blending Pentanol with WCO-based biodiesel in a Common Rail Direct Injection engine, maintaining a constant injection timing of 23° before Top Dead Center and a compression ratio of 17.5:1. The analysis covers various fuel compositions, including pure diesel (D100), 30% WCO-biodiesel (B30), 30% WCO-biodiesel with 10% Pentanol (B30 + P10), 30% WCO-biodiesel with 20% Pentanol (B30 + P20), 40% WCO-biodiesel (B40), 40% WCO-biodiesel with 10% Pentanol (B40 + P10), and 40% WCO-biodiesel with 20% Pentanol (B40 + P20), under varying load conditions. The results reveal that WCO-derived biodiesel blends demonstrate notable improvements in combustion and emission metrics. The B30 + P20 blend stands out, delivering a 9.9% increase in brake thermal efficiency, a 10.5% reduction in brake-specific fuel consumption (BSFC), and a 12.6% improvement in volumetric efficiency compared to pure diesel. Additionally, this blend enhances the heat release rate and cylinder pressure by 4.8% and 3.1%, respectively. Emission reductions are substantial, with CO, HC, and NOX emissions decreasing by 31.75%, 20.28%, and 14.82%, respectively, when compared to other biodiesel blends. This research underscores Pentanol-enhanced WCO-biodiesel blends as a sustainable and efficient alternative for automotive applications.